Combined David and Frozen Elephant Trunk Procedure in Acute Aortic Dissection - Goebel, Nora; Nagib, Ragi; Salehi-Gilani, Schahriar; Ahad, Samir; Albert, Marc; Ursulescu, Adrian; Franke, Ulrich F.W. (The Thoracic and Cardiovascular Surgeon, 2019)
Background Valve sparing aortic root repair by reimplantation (David procedure) is an established technique in acute aortic dissection Stanford type A involving the aortic root. In DeBakey type I dissection, aortic arch replacement using the frozen elephant trunk (FET) was introduced to promote aortic remodeling of the downstream aorta. The combination of these two complex procedures represents a challenging surgical strategy and was considered too risky so far.Methods All patients with acute aortic dissection DeBakey type I undergoing valve sparing aortic root repair by reimplantation technique of David combined with extended aortic repair using the FET at our center between October 2009 and December 2016 were evaluated. Outcomes are compared with patients who underwent prosthetic aortic root replacement and FET for aortic dissection in the same timeframe.Results A total of 28 patients received combined David and FET procedure, while 20 patients received prosthetic aortic root replacement and FET procedure. Thirty-day mortality was 10.7% (n = 3) for the David group and 20% (n = 4) for the root replacement group (p = 0.43). Postoperative echocardiographic control revealed an excellent aortic valve function with regurgitation grade 0° or maximum grade I° and a mean gradient of 4.3 ± 2.1 mm Hg in all patients in the David group versus 7.2 ± 2.4 mm Hg in the aortic root replacement group, p = 0.003. Computed tomography angiography scan showed positive aortic remodeling in all but three patients (91.9%). Mid-term follow-up survival was 82.1% in the David group and 68.4% in the root replacement group, p = 0.28. There was no need for reintervention at the root or descending aorta.Conclusion Simultaneous application of the David and FET procedure in patients with acute aortic dissection is safe and feasible in experienced hands as compared with standard aortic root replacement plus FET. The mid-term outcomes are encouraging and noninferior to conventional surgery results.
Keywords: aorta/aortic; Aortic valve and root; outcomes